Issues and Challenges of Affordable Housing and Housing Affordability in Malaysia: A Case Study of Residensi Wilayah (RUMAWIP) - Tengku Adnan, Tengku Mansor (2022)
This study examines the factors and challenges of the development of RESIDENSI GURNEYMAS, an affordable housing scheme in Kuala Lumpur. This is a qualitative study using in-depth interview methodology. 27 informants of RESIDENSI GURNEYMAS were selected, which included developers, contractors, local assemblymen, government officials, potential buyers, and existing buyers. Based on the literature reviews, the process of building affordable homes has numerous challenges and barriers, such as location, land issue, pricing, bank loan, as well as the lifestyle of the buyers. In this study, 11 challengers and barriers faced by development growth were identified. The challenges were high urbanisation rate, price exploitation, property price, household income, demand and supply, housing loan, the unclear definition of affordable housing, pricing policy, land conversion, and housing quality. The unstructured and semi structured questions were asked to 27 informants participated in the in-depth interviews. Information gathered from the in-depth interview and observation were taken by mnemonic writing and then analysed. The results of the study were tabulated based on eight organising themes and basic themes, such as high urbanisation, price manipulation, housed hold income, definition, pricing policy, bank loan and housing schemes policy. In conclusion, this study has formulated qualitative research on RESIDENSI WILAYAH and provided contribution to socioeconomic growth in Malaysia. The study also provides recommendation, implication, theoretical and practical issues to stakeholders in addressing affordable housing issues in Malaysia.